NPAS3 Regulates Transcription and Expression of VGF: Implications for Neurogenesis and Psychiatric Disorders - Yang, Dongxue; Zhang, Wenbo; Padhiar, Arshad; Yue, Yao; Shi, Yonghui; Zheng, Tiezheng; Davis, Kaspar; Zhang, Yu; Huang, Min; Li, Yuyuan; Sha, Li (Frontiers in Molecular Neuroscience, 2016)
NPAS3 (Neuronal PAS domain protein 3) and VGF (VGF Nerve Growth Factor Inducible) are important for neurogenesis and psychiatric disorders. Previously, we have demonstrated that NPAS3 regulates VGF at the transcriptional level. In this study, VGF (non-acronymic) was found regulated by NPAS3 in neuronal stem cells. However, the underlying mechanism of this regulation remains unclear. This studies aim was to explore the correlation of NPAS3 and VGF, and their roles in neural cell proliferation, in the context of psychiatric illnesses. Firstly, we focused on the structure of NPAS3, to identify the functional domain of NPAS3. Truncated NPAS3 lacking transactivation domain was also found to activate VGF, which suggested that not only transactivation domain but other structural motifs were involved in the regulation. Secondly, Mutated enhancer box (E-box) of VGF promoter showed significant response to this basic helix-loop-helix (bHLH) transcription factor, which suggested an indirect regulatory mechanism for controlling VGF expression by NPAS3. κB site within VGF promoter was identified for VGF activation induced by NPAS3, apart from direct binding to E-box. Furthermore, ectopically expressed NPAS3 in PC12 cells produced parallel responses for nuclear factor kappa-light-chain-enhancer of activated B cells [NF-κB (P65)] expression, which specifies that NPAS3 regulates VGF through the NF-κB signaling pathway. Over-expression of NPAS3 also enhances the cell proliferation, which can be blocked by knockdown of VGF. Finally, NPAS3 was found to influence proliferation of neural cells through VGF. Therefore, downstream signaling pathways that are responsible for NPAS3-VGF induced proliferation via glutamate receptors were explored. Combining this work and published literature, a potential network composed by NPAS3, NF-κB, Brain-Derived Neurotrophic Factor (BDNF), Nerve growth factor (NGF) and VGF, was proposed. This network collectively detailed how NPAS3 connects with VGF and intersected neural cell proliferation, synaptic activity and psychiatric disorders.